The Role of Entrepreneurial Orientation in Small Medium Enterprises Performance in Lagos, Nigeria - Ogbaini, Clement Aliu; Akpor, Afam Augustine; Oputa, John Edewor; Marvis, Vine Bello; Williams, Maureen Chinansa Ola; Okafor, Ndubuisi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This study examines the role of entrepreneurial orientation on the performance of Small and Medium Enterprises (SMEs) in Nigeria. The objective was to determine the effect of innovativeness, risk-taking, proactiveness, autonomy and competitive aggressiveness on the performance of SMEs in Nigeria. Using a 21-item questionnaire with a 5-point Likert scale, the authors collected data on entrepreneurial orientation and SMES Performance. Taro Yamani Formula determined the sample size of 222 SME owners, Managers and Workers. Collected data was analysed with the use of a frequency distribution table, and simple percentages and the hypotheses were tested with Chi-Square statistical formula. The study revealed that innovativeness, risk-taking, proactiveness and competitive aggressiveness enhance the performance of SMEs. The practice of autonomy does not enhance SMEs' performance. The research suggests that SME owners and managers should be creative and innovative to adapt to external changes and customer needs. They should take calculated risks, invest in new products and services, conduct competitor analysis, and encourage employee initiatives.